Multivariate data analysis for monitoring the quality of the commercialized bottled water in Bangladesh - Anwar, K M Mostafa (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management